2007
DOI: 10.1007/s11240-007-9325-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovering polyploid papaya in vitro regenerants as screened by flow cytometry

Abstract: Several protocols have been proposed for in vitro propagation of papaya, either based on somatic embryogenesis or shoot organogenesis. It is well-known that tissue culture-based approaches are frequently associated with somaclonal variation. Whether on the one hand this phenomenon can preclude further stages of in vitro culture, on the other hand it can generate useful genetic variability for crop improvement. However, somaclonal variation analyses are limited in papaya tissue culture. The DNA ploidy level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 52 publications
4
40
0
1
Order By: Relevance
“…This observation is consistent with the findings of Clarindo et al (2008) and Anandan et al (2012), who reported asynchronous maturation of C. papaya SE in a medium supplemented with ABA. ABA has been the most indicated PGR for regulating SE maturation in vitro (Chen and Chen 1992, Castillo et al 1998a, Anandan et al 2012.…”
Section: Somatic Embryogenesis and In Vitro Regenerationsupporting
confidence: 93%
See 3 more Smart Citations
“…This observation is consistent with the findings of Clarindo et al (2008) and Anandan et al (2012), who reported asynchronous maturation of C. papaya SE in a medium supplemented with ABA. ABA has been the most indicated PGR for regulating SE maturation in vitro (Chen and Chen 1992, Castillo et al 1998a, Anandan et al 2012.…”
Section: Somatic Embryogenesis and In Vitro Regenerationsupporting
confidence: 93%
“…Accordingly, Anandan et al (2012) also observed a high rate of pro-embryogenic calli (75.12%) from zygotic embryos of C. papaya Co7 . As reported by Monmarson et al (1995), Clarindo et al (2008) and Anandan et al (2012), zygotic embryos of papaya show high-embryogenic potential and quick response to tissue culture conditions. Comparatively, Fitch (1993) observed a callogenic response from hypocotyl segments between the 10th and 14th weeks, as did Castillo et al (1998a) around the sixth week.…”
Section: Somatic Embryogenesis and In Vitro Regenerationsupporting
confidence: 53%
See 2 more Smart Citations
“…1a). This response characterized the somatic embryogenesis process as asynchronous, which is commonly observed in some species such as C. arabica (Quiroz-Figueroa et al 2002), C. papaya (Clarindo et al 2008 and Vitis vinifera L. (Jayasankar et al 1999). Furthermore, emergence of secondary somatic embryos from primary ones was also observed (Fig.…”
Section: In Vitro Development Of Somatic Embryos and Plantlet Regenermentioning
confidence: 76%